2019
DOI: 10.3389/fnins.2019.00402
|View full text |Cite
|
Sign up to set email alerts
|

Does Sensory Retraining Improve Sensation and Sensorimotor Function Following Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: Reduced sensation is experienced by one in two individuals following stroke, impacting both the ability to function independently and overall quality of life. Repetitive activation of sensory input using active and passive sensory-based interventions have been shown to enhance adaptive motor cortical plasticity, indicating a potential mechanism which may mediate recovery. However, rehabilitation specifically focusing on somatosensory function receives little attention. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 48 publications
(172 reference statements)
4
57
0
1
Order By: Relevance
“…Somatosensory therapy can improve somatosensory function. Serrada et al (11) reported a moderate positive effect for passive somatosensory therapy such as peripheral stimulation, thermal stimulation and intermittent compression therapy. No evidence was presented for active somatosensory therapy such as somatosensory discrimination training due to heterogeneity in outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Somatosensory therapy can improve somatosensory function. Serrada et al (11) reported a moderate positive effect for passive somatosensory therapy such as peripheral stimulation, thermal stimulation and intermittent compression therapy. No evidence was presented for active somatosensory therapy such as somatosensory discrimination training due to heterogeneity in outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Somatosensory impairment is considered to have a negative prognostic impact on rehabilitation interventions and overall motor function recovery (Bowerman et al, 2012 ; Dietz and Fouad, 2014 ; Zandvliet et al, 2020 ). Although the current literature in this field is limited, a recent systematic review and meta-analysis indicated positive effects in improving somatosensory impairments (Serrada et al, 2019 ). Specifically, sensory discrimination training by repeated practice to distinguish textures and localize tactile stimuli can influence the sensory system and drive recovery (Carey et al, 1993 ; Yekutiel and Guttman, 1993 ; Turville et al, 2019 ).…”
Section: Clinical Approaches For Stimulating Somatosensation In Home-mentioning
confidence: 99%
“…Furthermore, somatosensory deficits significantly impair motor control, impede functional performance 2,[4][5][6][7] and negatively impact quality of life. 8 Though somatosensation has an important role in the functioning of the upper limb 7 and is routinely assessed clinically, 7 interventions that address somatosensory deficits are lacking.…”
Section: Introductionmentioning
confidence: 99%